MENGENALKAN BAHASA INGGRIS UNTUK ANAK USIA DINI DENGAN MEDIA FLASH CARD DI POS PAUD MAWAR 19 DEPOK - Puji Yulianty; Purwati Purwati (Jurnal Anak Bangsa, 2022)
English in this globalization era, being able to speak English is not only a good idea but a must. Because it is very important and learning English will be better if done from an early age. Early age is the age which is the golden age which is the age of children who easily receive information easily and quickly. To make it easier to introduce English to early childhood using learning media. Learning media is an intermediary that is useful as a messenger that aims to provide real, concrete and efficient experience so that learning objectives are achieved. One effective way to introduce English to early childhood is with flashcard media. Flashcards are teaching media in the form of small cards, usually the size is adjusted to the size of the class size, contains images, text, signs, symbols that have two front and back sides, namely the image side and the word side in English and in Indonesian, is a description of the image. Teachers who are creative and innovative will be liked and will provide teaching according to the level of child development, therefore introducing English to early childhood with flashcard media and how to play it will certainly be liked by children and is an interesting method to introduce language. English in addition to the singing method. Therefore, the Mawar 19 POS PAUD teacher after participating in the training to introduce English to early childhood through flashcards will become even more creative and provide interesting learning